2010
DOI: 10.1007/s10661-010-1806-8
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of PM10 concentrations at different locations in Malaysia

Abstract: Malaysia has experienced several haze events since the 1980s as a consequence of the transboundary movement of air pollutants emitted from forest fires and open burning activities. Hazy episodes can result from local activities and be categorized as "localized haze". General probability distributions (i.e., gamma and log-normal) were chosen to analyze the PM(10) concentrations data at two different types of locations in Malaysia: industrial (Johor Bahru and Nilai) and residential (Kota Kinabalu and Kuantan). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Meanwhile, Sansuddin et al, [24] concluded that the best time series model at four different locations, which represented industrial (Nilai and Johor Bharu) and residential (Kota Kinabalu and Kuantan), had been the AR. The seasonal ARIMA was also used to predict the ozone precursor at Brazil [25].…”
Section: Univariate Time Series Modellingmentioning
confidence: 99%
“…Meanwhile, Sansuddin et al, [24] concluded that the best time series model at four different locations, which represented industrial (Nilai and Johor Bharu) and residential (Kota Kinabalu and Kuantan), had been the AR. The seasonal ARIMA was also used to predict the ozone precursor at Brazil [25].…”
Section: Univariate Time Series Modellingmentioning
confidence: 99%
“…Sharma et al (2013b) have also observed that 24 hour average PM 10 concentrations follow lognormal distribution at three different locations in Delhi city. However, the topographical and geographical characteristics of the site may affect the particle distribution (Taylor et al, 1986;Sansuddin et al, 2011).…”
Section: The Study Location Aph-2mentioning
confidence: 99%
“…The PDF plot was used to identify the skewness of the distribution and it plot by using the value of parameter estimation [18]. The derivation of PDF was used for prediction of exceedences [19] and the CDF was used to determine the probability of air pollutant concentration [20]. Table 1 shows the PDF and the parameter estimation used [21].…”
Section: Probability Distributionmentioning
confidence: 99%